Anti-corrosion pretreatment agent, treatment method using anti-corrosion pretreatment agent and product of anti-corrosion pretreatment agent
By using an anti-corrosion pretreatment agent containing a solvent, an inorganic inhibitor, a silane compound and a bifunctional epoxy resin precursor, the problem of chromium-free pretreatment and corrosion prevention in the prior art is solved, and efficient corrosion and adhesion of the surface of light metal materials is achieved.
Patent Information
- Application Number
- CN202280098034.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-14
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively provide chromium-free pretreatment methods, which not only ensure the corrosion resistance of light metal materials, but also avoid the use of strong acids, large amounts of organic solvents and high fluoride concentrations.
An anti-corrosion pretreatment agent comprising a solvent, an inorganic inhibitor, a silane compound and a bifunctional epoxy resin precursor is used, which forms an anti-corrosion film by thermal curing and does not contain an organic solvent.
It achieves good corrosion resistance and adhesion on the surface of light metal materials, meets application needs in the fields of home appliances, construction, etc., and avoids the risk of using harmful chemicals.
Smart Images

Figure BDA0005234678010000161 
Figure BDA0005234678010000171 
Figure BDA0005234678010000211
Abstract
Description
Technical Field
[0001] The present invention relates to an anti-corrosion pretreatment agent and a method for treating the surface of a metal substrate coated with zinc or a zinc alloy, aluminum or an aluminum alloy, or magnesium or a zinc-magnesium alloy. The agent is particularly suitable for treating the surface of coil coatings for use on these substrates in the home appliance, construction, and automotive industries. Articles containing such metal substrate surfaces treated with the anti-corrosion pretreatment agent exhibit good corrosion resistance and improved adhesion to the treated surface. Background of the Invention
[0003] Among the metal materials in actual use, light metals such as zinc, aluminum, and magnesium are the lightest and have high specific strength. Therefore, they have been widely used in various fields, such as interior and exterior parts of automobiles and two-wheeled vehicles, home appliance accessories, storage containers (such as bags and suitcases), sports equipment, optical instruments and tool parts, sticks, and other emerging areas of the electronics industry (such as computers, audio equipment, etc.). However, light metals, especially magnesium, are the most reactive metals and are difficult to use directly without any treatment due to their low corrosion resistance.
[0004] According to the prior art, coil coating processes primarily consist of three sub-steps. In the first step, the metal sheet is cleaned and coated with an inorganic pretreatment layer; in the second step, a primer is applied; and in the final third step, a topcoat is applied. In some applications, a clearcoat or protective film coating may also be applied. Attempts have been made to provide the functions that facilitate the aforementioned pre-applied coatings solely through the pretreatment step.
[0005] When electrodeposition coating or paint coating (e.g., water-based coating, solvent coating, powder coating, etc.) is applied to the surface of a metal substrate, the surface of the metal substrate is chemically treated before the coating is formed to form a chemical conversion film, thereby improving properties such as corrosion resistance and adhesion to the coating film. For example, for this purpose, a suitable organic polymer is added to the inorganic conversion treatment process, and the polymer is capable of forming a surface film that exhibits the functional properties required of the pre-applied coating.
[0006] DE 199 23 118 A1 discloses a polymerizable composition for an organic coating of a metal substrate, and a method for protecting a steel substrate with an organic / inorganic hybrid polymer film based on an alkoxysilane, another condensable organometallic compound of the formula M(OR) 4 , (meth)acrylic acid, water, and a polymerization initiator. The coating cures by thermal or photopolymerization. Zirconium and titanium are mentioned as metals of the organometallic compound. The document states that the film protects the steel substrate from corrosion and oxidation, and that the coating is also intended to protect the substrate from impact and other mechanical effects.
[0007] DE19751153A discloses polymerizable compositions containing titanium, manganese, and / or zirconium salts of ethylenically unsaturated polymerizable carboxylic acids, other ethylenically unsaturated comonomers, and free-radical polymerization initiators suitable for organic coil coating of metallic materials. These non-aqueous metal coatings are suitable for chromium-free pretreatment of steel and offer good corrosion control.
[0008] DE 197 54 108 A1 describes a chromium-free aqueous anticorrosion composition for the treatment of galvanized or alloy-galvanized steel surfaces and aluminum surfaces. The composition is particularly suitable for treating metal strips to protect them from corrosion, with or without subsequent painting, and is preferably applied to the surface in such a way that a dry layer coating is produced.
[0009] Despite the extensive prior art, there remains a need for improved corrosion inhibitors and metal surface coating methods that enable chromium-free pretreatment of metal substrates, provide good corrosion protection, while avoiding strong acids, large amounts of organic solvents, and high fluoride concentrations.
[0010] A variety of metal substrates, including aluminum, aluminum alloys, zinc, zinc alloys, magnesium, and zinc-magnesium alloys, are widely used in color-coated steel. Due to the different characteristics of these substrates, it is difficult to treat them all with the same pretreatment agent on a single production line, especially on the same color coil production line.
[0011] Therefore, an object of the present invention is to provide a pretreatment agent for light metal materials (particularly aluminum or its alloys, zinc or its alloys, magnesium or zinc-magnesium alloys) which can eliminate the problems associated with conventional surface treatment compositions. Summary of the Invention
[0012] The present invention relates to an anti-corrosion pretreatment agent that is alkaline or acidic. The agent does not contain an organic solvent. The anti-corrosion pretreatment agent can directly react with a metal substrate. The anti-corrosion pretreatment agent is cured by thermal curing and forms an anti-corrosion pretreatment on the metal substrate. The anti-corrosion pretreatment exhibits good anti-corrosion performance and tightly connects the substrate to a primer.
[0013] The present invention also relates to an anti-corrosion pretreatment agent comprising: a) a solvent; b) at least one inorganic inhibitor; c) at least one silane compound; and d) a bifunctional epoxy resin precursor (C), wherein the bifunctional epoxy resin precursor (C) is represented by the following formula: R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n-R2, wherein, independently, X = -COO-, a sulfide group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; Y = -COO-, a sulfide group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H; R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms; R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4; R3 is any type of chain as long as it connects two hydroxyl α-carbon atoms; n is an integer from 1 to 10.
[0014] The present invention also relates to a method for treating a metal surface using the anti-corrosion pretreatment agent according to the present invention, the method comprising the following steps: a) contacting the anti-corrosion pretreatment agent according to any one of the preceding embodiments with a metal surface at a process temperature of at least 40°C but not higher than 200°C, thereby forming a film on the metal surface; b) optionally removing excess anti-corrosion pretreatment agent from the surface; and c) curing the coating on the surface by a thermal method or by high-energy irradiation for at least 10-5 seconds at a process temperature of 50-90°C to form a cured coating.
[0015] The present invention also relates to an article, at least a portion of which includes a surface treated according to the present invention. The surface of the article is treated with the anti-corrosion pretreatment agent according to the present invention or by the treatment method according to the present invention. The surface-treated article exhibits excellent corrosion resistance and improved adhesion (before and after aging) in appliance and construction applications. DETAILED DESCRIPTION
[0016] In the following paragraphs, the present invention will be described in more detail. Each aspect described in this manner may be combined with any other aspect or aspects unless otherwise indicated. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature or features indicated as being preferred or advantageous.
[0017] In the context of the present invention, unless the context requires otherwise, the terms used are to be interpreted according to the following definitions.
[0018] As used herein, the singular forms "a," "an," and "the" include both singular and plural referents unless the context clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally understood to include "and / or" unless the context clearly dictates otherwise.
[0019] As used herein, the terms “comprising,” “comprises,” and “comprised of” are synonymous with “including,” “includes,” or “containing,” and are inclusive or open-ended and do not exclude other unrecited members, elements, or process steps.
[0020] The recitation of numerical endpoints includes all numbers and fractions subsumed within the corresponding range, as well as the recited endpoint.
[0021] Unless otherwise defined, all terms used in the disclosure of the present invention, including technical and scientific terms, have the meanings commonly understood by those skilled in the art to which the present invention belongs. By way of further guidance, term definitions are included in this specification for a better understanding of the teachings of the present invention.
[0022] In the context of this disclosure, several terms will be used.
[0023] The term "polymer" is used herein in accordance with its common usage in chemistry. A polymer is composed of many repeating subunits. The term "polymer" is used to describe the resulting material formed by a polymerization reaction.
[0024] Unless the context requires otherwise, the terms aluminum or zinc as used herein include pure metals and alloys and are hereinafter referred to simply as "aluminum" or "zinc."
[0025] The terms "mass" and "weight" are used synonymously herein. Therefore, unless otherwise indicated, "weight percent" (wt%) refers to the mass (weight) percentage based on the entire composition or the mass content percentage based on all molecules.
[0026] The term "chromium-free" as used herein in connection with the compositions described means that the composition comprises less than 100 ppm, preferably less than 10 ppm, particularly preferably less than 1 ppm, of chromium, based on the total composition of chromium compounds, in each case calculated as Cr2O3.
[0027] The terms "water-based" or "aqueous" as used herein with respect to the compositions described herein indicate that the composition is liquid and comprises water as the primary solvent. In various embodiments, at least 50% by weight, or at least 60% by weight, preferably at least 70% by weight, and even more preferably at least 90% by weight of the solvent of the composition, based on the total weight of the composition, is water.
[0028] A newly prepared or newly cleaned metal surface that has not adopted any anti-corrosion measures is contacted with the anti-corrosion pretreatment agent according to the present invention, and the anti-corrosion pretreatment agent is solidified, and an anti-corrosion pretreatment is formed on the metal sheet surface. In this way, the treated metal surface obtained has corrosion resistance. The metal sheet can be stored and / or transported in this form. In addition, it can also be cut into blocks, optionally shaped, and joined to form a structural unit according to other blocks. The metal surface that has been coated with the anti-corrosion pretreatment agent according to the present invention can also be coated with other additional decorative / functional coatings, such as primers and topcoats.
[0029] Alternatively, the surface of a metal sheet coated with the anti-corrosion pretreatment agent according to the present invention, or metal sheets cut therefrom, can be coated with at least one additional decorative or functional coating, such as a topcoat or primer, prior to commercialization and / or further processing into subassemblies. In this case, the anti-corrosion pretreatment agent according to the present invention serves as a corrosion protector and a connector between the "substrate" and the "additional coating." The anti-corrosion coating also provides good adhesion between the "additional coating" and the metal substrate. For pre-coated sheets, this good adhesion can meet the molding requirements in subsequent operations. Consequently, it can reduce certain failure scenarios, such as paint film powdering, blistering, and cracking.
[0030] Anti-corrosion pretreatment agent
[0031] The present invention relates to an anti-corrosion pretreatment agent comprising: a solvent, a bifunctional epoxy resin precursor (C), at least one inorganic inhibitor, and at least one silane compound. In some embodiments, the anti-corrosion pretreatment agent is an acidic aqueous dispersion. In some embodiments, the anti-corrosion pretreatment agent is an alkaline aqueous dispersion. In some embodiments, the anti-corrosion pretreatment agent further comprises one or more resins selected from the group consisting of a polyurethane resin (A), a polyurethane-acrylic resin (B), and a polyacrylic-epoxy resin (D).
[0032] Bifunctional epoxy resin precursor (C)
[0033] The difunctional epoxy resin precursor (C) of the present invention can be commercially obtained or prepared by a known method, such as reacting a difunctional epoxy compound with a nucleophilic or electrophilic compound having an active hydrogen atom.
[0034] In some embodiments of the present invention, the difunctional epoxy resin can be reacted with a polymer having a hydroxyl group (-OH), a polymer having an ester group (-COOR), an organic / inorganic acid containing a heteroatom (N, S, P), or an amino compound to prepare a difunctional epoxy resin precursor (C).
[0035] The epoxy compound used in the preparation is not particularly limited in type as long as it contains at least two epoxy groups in its molecule.
[0036] The two epoxy groups can generate two hydroxyl groups of the bifunctional epoxy resin precursor (C).
[0037] This difunctional epoxy compound comprises bisphenol A epoxy, bisphenol F epoxy, acryl (acryl) modified epoxy, the epoxy ester obtained by epoxy and unsaturated fatty acid reaction, carbamate modified epoxy, silane modified epoxy, halogenated epoxy alkylene oxide (for example epihalohydrin), phosphoric acid modified epoxy resin, and the epoxy compound with two or more glycidyl groups.Above-mentioned epoxy resin can be used alone, also can two or more combinations be used.The epoxide equivalent weight of epoxy resin of the present invention is approximately 100 grams / equivalent to approximately 2000 grams / equivalent.
[0038] The rigidity and appropriate flexibility of the polyhydroxyl and heteroatom structural units derived from the difunctional epoxy resin precursor (C) can improve the adhesion of the pretreatment coating. In addition, this structure is difficult to hydrolyze and can improve adhesion, and can also improve the corrosion resistance of the pretreatment coating. The hydroxyl groups in the dihydroxy-functionalized epoxy resin precursor can be firmly bonded to the metal substrate due to their polarity and help improve adhesion to the metal substrate. In addition, the heteroatom structure (OC, NC, SC, PC) also helps to establish a strong bond with the metal substrate. During the processing of the pretreatment coating, the hydroxyl groups in the epoxy resin precursor (C) are cross-linked with the zirconium compound and the compound containing silanol groups, thereby improving the chemical resistance and corrosion resistance of the coating.
[0039] The epoxy resin precursor (C) is preferably used in the form of an aqueous dispersion thereof. If necessary, the aqueous dispersion of the bifunctional epoxy resin precursor (C) may further contain a dispersant such as a surfactant.
[0040] The weight average molecular weight of the bifunctional epoxy resin precursor (C) is preferably 200 to 10,000.
[0041] The pH value of the bifunctional epoxy resin precursor (C) is not particularly limited.
[0042] The content ratio of the difunctional epoxy resin precursor (C) to the total mass of the solid content is preferably 20.0% to 85% by weight, or 21% to 80% by weight, or 25% to 70% by weight. If this content ratio is less than 20% or less than 25% by weight, the T-bend test will fail; and if this content ratio exceeds 70% or 80% by weight, chemical resistance will be negatively affected.
[0043] In some embodiments, an epoxy resin may be reacted with a polymer having functional groups, an organic / inorganic acid having heteroatoms (N, S, P), and an amino group to produce a difunctional epoxy resin precursor.
[0044] In some embodiments, bisphenol A epoxy is reacted with orthophosphoric acid and propylene glycol monomethyl ether to produce a phosphoric acid-modified epoxy resin.
[0045] In some embodiments, bisphenol A epoxy is reacted with citric acid and propylene glycol monomethyl ether to produce a carboxyl group-modified epoxy resin.
[0046] In some embodiments, the difunctional epoxy resin precursor has the formula:
[0047] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2
[0048] Among them, independently,
[0049] X = -COO-, thiol, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; preferably -COO-, -P(OR)(OH)-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- comprises an aliphatic chain having 1 to 5 carbon atoms;
[0050] Y = -COO-, thio group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; preferably -COO-, -P(OR)(OH)-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- contains an aliphatic chain having 1 to 5 carbon atoms;
[0051] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H; preferably 1 to 10 carbon atoms or H;
[0052] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms; preferably 1 to 10 carbon atoms;
[0053] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4; preferably 1 to 10 carbon atoms;
[0054] R3 is any type of chain as long as it connects two hydroxyl α-carbon atoms; preferably, R3 is selected from the group consisting of: aromatic or aliphatic groups having 1 to 20 carbon atoms, polyurethane groups, aliphatic or aromatic alkanes having 2 to 20 carbon atoms, and acrylate-containing polymer groups.
[0055] n is an integer of 1 to 10, preferably an integer of 2 to 8.
[0056] In some embodiments, the difunctional epoxy resin precursor has the formula:
[0057] HX-R4-X-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -H,
[0058] Among them, independently,
[0059] X=-COO-, -P(OR)(OH)-O-;
[0060] R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms;
[0061] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;
[0062] n is an integer from 2 to 8.
[0063] solvent
[0064] The anti-corrosion pretreatment agent of the present invention comprises a solvent, such as water, to dissolve all components, thereby forming a coating dispersion. In some embodiments, water is used to dilute the surface treatment composition of the present invention, and it provides relatively long-term stability for the composition. For example, under the same storage conditions, compared with a surface treatment composition having a water content of about 60 wt % or higher, a composition having a water content lower than about 40 wt % is more likely to polymerize or "gel". Although the anti-corrosion pretreatment agent of the present invention typically applied to a substrate contains about 70 wt % or more water, such as 85 wt %, it should be understood that the anti-corrosion pretreatment agent of the present invention also includes a concentrated formulation composition having a water content of 50 wt % to 85 wt %. The end user only needs to dilute the concentrated formulation with additional water to obtain the optimal anti-corrosion pretreatment agent concentration for a specific surface treatment application.
[0065] In some embodiments of the present invention, deionized water is preferably used as the solvent. In some embodiments of the present invention, the solvent content of the anti-corrosion pretreatment agent is 50 wt % to 85 wt %, or 60 wt % to 85 wt %, or 65 wt % to 75 wt %, based on the total weight of the anti-corrosion pretreatment agent.
[0066] The anti-corrosion pretreatment agent of the present invention can be provided as a ready-to-use anti-corrosion pretreatment agent, as a concentrated anti-corrosion pretreatment agent to be diluted with water before use, as a supplementary composition or as a multi-component coating system.
[0067] As used herein, "aqueous solution" means that the anti-corrosion pretreatment agent contains at least 50% by weight, or at least 60% by weight, or at least 65% by weight, of water, based on the total weight of the composition. In addition to water, other suitable solvents include those particularly useful in water-based coating technologies. Examples of other suitable solvents include, but are not limited to: water-compatible solvents such as alcohols or ethers, more specifically, methanol and ethanol; glycols such as dipropylene glycol; and other glycol ethers such as propylene glycol monobutyl ether and dipropylene glycol monobutyl ether.
[0068] pH value of the anti-corrosion pretreatment agent
[0069] In some embodiments, the anti-corrosion pretreatment agent is an acidic aqueous dispersion.
[0070] The pH value of the anti-corrosion pretreatment agent is greater than 2.7 and less than 7, or 2.9 to 6.5, or 3.0 to 6.0, or 3.5 to 5.5, or 4.0 to 5.0. The lower limit of the pH value is 2.7, 2.8, 2.9, 3.0, 3.5, 4.0, 4.5 or 5.0; the upper limit of the pH value is less than 7, or 6.5, or 6.0, or 5.5, or 5.2, or 5.0. If necessary, one or more optional pH adjusters, including small amounts of inorganic acids, alkaline components and organic acids, can be used to adjust the pH value to the above desired operating pH value. An anti-corrosion pretreatment agent with an alkaline operating pH value will produce a better anti-corrosion effect.
[0071] The pH value of the aqueous anti-corrosion pretreatment agent is in the range of 3.0 to 6.0, preferably in the range of 4.0 to 5.0. In other words, the aqueous anti-corrosion pretreatment agent according to the present invention is an acidic solution or acidic dispersion.
[0072] In some embodiments, the anti-corrosion pretreatment agent is an alkaline aqueous dispersion.
[0073] The pH value of the anti-corrosion pretreatment agent is greater than 7 to 12, or 7.5 to 12, or 8 to 12, or 8.1 to 11.5. The lower limit of the pH value is 7.1, 7.5, 8.0, 8.1 or 8.2; the upper limit of the pH value is 12, or 11.8, or 11.6, or 11.5, or 11.2, or 11.0, or 10.0, or 9.5, or 9.2, or 9.0, or 8.8, or 8.5. If necessary, one or more optional pH adjusters, including small amounts of inorganic acids, alkaline components and organic acids, can be used to adjust the pH value to the above desired operating pH value. An anti-corrosion pretreatment agent with an alkaline operating pH value will produce better anti-corrosion effect.
[0074] The pH value of the aqueous anti-corrosion pretreatment agent is in the range of 7.1 to 12, preferably in the range of 8 to 12. In other words, the aqueous anti-corrosion pretreatment agent according to the present invention is an alkaline solution or alkaline dispersion.
[0075] <Inorganic inhibitors>
[0076] The inorganic inhibitor of the present invention can be selected by a known method according to the pH value of the anti-corrosion pretreatment agent.
[0077] In some alkaline embodiments, the zirconium compound is used as a film-forming component to form a three-dimensional cross-linked zirconium oxide coating by hydrolysis and condensation reaction, while accompanying the desorption of volatile acids in the aqueous system during curing, and can have a positive impact on corrosion resistance and adhesion to substrates. The selected zirconium compound should be stable in alkaline aqueous solution. The zirconium compound is not particularly limited in type, as long as it contains a zirconium atom, and examples thereof include basic zirconium carbonate, zirconium carbonate salts (such as sodium zirconium carbonate, potassium zirconium carbonate, lithium zirconium carbonate and ammonium zirconium carbonate), zirconium hydroxide, zirconium lactate, zirconium acetate, zirconium nitrate, zirconium sulfate, zirconium chloride, calcium zirconate, zirconium ethoxide (zirconium ethoxide) and zirconium hexafluoroacetylacetonate. Wherein, with regard to excellent corrosion resistance, ammonium zirconium carbonate and sodium zirconium carbonate are preferred. The zirconium compound is selected from ammonium zirconium carbonate, potassium zirconium carbonate, basic zirconium oxide and zirconium acetate.
[0078] In some alkaline embodiments, the inorganic inhibitor is a metal compound, such as a vanadium compound. The metal material may have a three-dimensional shape, such as a structure made of a metal sheet. The metal compound containing metal atoms is not particularly limited in type as long as it contains a metal, and examples thereof include the above-mentioned metal oxides and / or metal alkoxides containing metal atoms. The supply source of the metal ion can be at least one metal compound selected from ammonium salts and acetonates of, for example, Mo, W, Y, Bi, Mn, La, Ce, Sm, Zn, Al, Si, Ni, Co, Zr, Mg, Ti, and V. Among them, compounds that can be dissolved in alkaline solutions are preferred. For example, vanadium compounds such as vanadium pentoxide, vanadium trioxide, vanadium oxyacetylacetonate, vanadium acetylacetonate, etc.
[0079] In some basic embodiments, the mass ratio of the content of the metal material and the organosilane [M / silane] is 1 to 5, preferably 2 to 4. If the solid content mass ratio is less than 1, no corrosion resistance effect will be exhibited, while if the ratio is higher than 5, the system will have difficulty maintaining stability and chemical resistance will be negatively affected.
[0080] In the alkaline aqueous anti-corrosion pretreatment agent, the content of the inorganic inhibitor is 0.3 wt % to 7.0 wt %, or 0.5 wt % to 6.5 wt %, or 1.5 wt % to 6.3 wt %, or 1.7 wt % to 6.1 wt %, or 2.0 wt % to 4.0 wt %, or 3.0 wt % to 4.0 wt %, based on the weight of the solid content in the anti-corrosion pretreatment agent.
[0081] In some acidic embodiments, the inorganic inhibitor comprises at least one water-soluble or water-dispersible fluorinated acid or salt thereof, wherein the fluorinated acid is defined by the following general empirical formula: m T q F p O n ,
[0082] in:
[0083] q and p each represent an integer from 1 to 10;
[0084] m and n each represent an integer from 0 to 10; and
[0085] T is an element selected from Ti, Zr, Hf, Si, Sn, Al, Ge, and B.
[0086] In some acidic embodiments, the inorganic inhibitor comprises at least one fluoric acid selected from the group consisting of fluorotitanic acid (H2TiF6), fluorozirconic acid (H2ZrF6), fluorosilicic acid (H2SiF6), fluoroboric acid (HBF4), fluorostannic acid (H2SnF6), fluorogermanic acid (H2GeF6), fluorohafnic acid (H2HfF6), and fluoroaluminates (H3AlF6). In some preferred embodiments, the inorganic inhibitor comprises at least one fluorinated acid selected from the group consisting of fluorotitanic acid (H2TiF6), fluorozirconic acid (H2ZrF6), and fluorosilicic acid (H2SiF6).
[0087] One or more H atoms of the fluorinated acid may be replaced by a suitable cation (eg, ammonium, alkaline earth metal cation, or alkali metal cation) provided that the salt is water-soluble or water-dispersible.
[0088] The presence of free fluoride ions in the passivating composition that are not bound in complex form is not excluded, since the fluoride anions can act as promoters for the formation of the coating and are present at the interface between the coating and the metal substrate. Such free fluoride can be included by adding, for example, the following to the passivating composition anions: hydrofluoric acid; alkali metal fluorides, such as sodium fluoride; alkali metal fluorides, such as sodium fluoride; ammonium fluoride.
[0089] In some embodiments of the present invention, the acidic anti-corrosion pretreatment agent should comprise a fluorinated acid or a salt thereof, so that the molar concentration of the metal (T) in the aqueous composition is generally 0.1-1.0 mol / L, but more preferably 0.2-0.8 mol / L.
[0090] <Silane Compound>
[0091] The anti-corrosion pretreatment agent of the present invention further comprises a silane compound as a coupling agent. The silane coupling agent of the present invention can be selected according to the pH value of the anti-corrosion pretreatment agent.
[0092] While the exact composition of the silane coupling agent is not critical to the present invention, preferred silane coupling agents conform to the following general formula: y R r SiX x , wherein R represents an alkyl group; X represents a group selected from methoxy and ethoxy; Y represents a group selected from vinyl, mercapto, glycidoxyalkyl or methacryloxyalkyl; each of r, x and y is an integer independently selected from 1 to 3, but r may also be zero, and r+x+y=4.
[0093] More preferably, the silane coupling agent component is selected from the group consisting of vinyltrimethoxysilane, vinyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and mixtures of any two or more thereof.
[0094] Silane coupling agents having the above general formula are preferred among acidic anti-corrosion pretreatment agents because they have good solubility in the aqueous solution used to contact the metal surface in the process of the present invention and contribute greatly to improving the corrosion resistance of the pretreatment coating formed on the metal surface.
[0095] In some alkaline embodiments, the silane coupling agent of the present invention includes a silanol group-containing compound, which is a hydrolyzate of an organosilicon compound having a glycidoxyl group. The hydrolysis of the organosilicon can be carried out within a pH range of 8 to 10. As a hydrolysis aid, alkaline materials such as ammonia and organic amines are preferred because they evaporate during the coating formation process and are unlikely to remain in the pretreatment coating.
[0096] There is no limitation on the silane coupling agent used in the alkaline pretreatment agent as long as the silane coupling agent is compatible with the rare earth element-containing compound (eg, water-soluble zirconium salt and other components contained therein).
[0097] The silane coupling agent may have amino functional groups or epoxy functional groups. The amino or epoxy functional silane may contain C2-C10 alkoxy groups.
[0098] In some embodiments of the present invention, the silane coupling agent may have the general formula XY(Z) n Si(OH) 3-n , wherein, independently, X is a glycidoxy group or a functional group derived from a glycidoxy group, Y is a C1 to C10 alkylene group, Z is a methoxy group, an ethoxy group or a methyl group, and n is an integer from 0 to 2.
[0099] Some exemplary epoxy-functional silanes include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, or β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0100] Suitable amine-functionalized silane coupling agents for use in the surface treatment composition of the present invention have the following structure: (R2-O)3-Si-R3-NH2, wherein R2 is an alkyl group containing 1 to 10 carbon atoms, preferably 1 to 6 carbon atoms, most preferably a methyl group, and R3 is an alkylene group containing 1 to 10 carbon atoms, optionally substituted with an amino group. Examples of amine-functionalized silane coupling agents are aminomethylaminopropyltrimethoxysilane ((MeO)3-Si-(CH2)3-NH-(CH2)-NH2), aminopropyltrimethoxysilane ((MeO)3-Si-(CH2)3-NH2) and / or aminopropyltriethoxysilane ((EtO)3-Si-(CH2)3-NH2).
[0101] Other examples of silane coupling agents suitable for use in the present invention include, but are not limited to, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltri(2-ethylhexyloxy)silane, N -(6-aminohexyl)aminopropyltrimethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, o-aminophenyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-2-aminoethyl-3-aminopropyltrimethoxysilane, aminopropyltrimethoxysilane, aminopropylmethyldimethoxysilane, aminopropyltriethoxysilane, aminopropylmethyldiethoxysilane, aminophenyltrimethoxysilane, 4-amino-3-dimethylbutyltrimethoxysilane, 4-amino-3-dimethylbutylmethyldimethoxysilane, 4-amino-3-dimethylbutyltriethoxysilane, 4-amino-3-dimethylbutylmethyl Diethoxysilane, N-phenyl-aminopropyltrimethoxysilane, N-naphthyl-aminopropyltrimethoxysilane, N-phenyl-aminopropylmethyldimethoxysilane, N-naphthyl-aminopropylmethyldimethoxysilane, N-(n-butyl)aminopropyltrimethoxysilane, N-(n-butyl)aminopropylmethyldimethoxysilane, N-ethyl-aminopropyltrimethoxysilane, N-ethyl-aminopropylmethyldimethoxysilane, N-methyl-aminopropyltrimethoxysilane, N-methyl-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-aminopropyltrimethoxysilane, N-β-(aminoethyl)-aminopropyltriethoxysilane silane, N-β-(aminoethyl)aminopropylmethyldimethoxysilane, N-β-(aminoethyl)aminopropylmethyldiethoxysilane, N-3-[amino(dipropyleneoxy)]aminopropyltrimethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, bis(trimethoxysilylpropyl)amine, (3-trimethoxysilylpropyl)diethylenetriamine, (aminoethylamino)-3-isobutyldimethylmethoxysilane, (cyclohexylaminomethyl)triethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, (phenylaminomethyl)methyldimethoxysilane, 11-aminoundecyltriethoxysilane, 2-(2-pyridylethyl)thiopropyltrimethoxysilane, 2-(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, 3-(1,3-dimethylbutylene)aminopropyltriethoxysilane, 3-(2-imidazolin-1-yl)propyltriethoxysilane, 3-(m-aminophenoxy)propyltrimethoxyaminopropylsilanetriol, 3-(m-aminophenoxy)propyltrimethoxysilane, 3-(N,N ... methylaminopropyl)trimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltris(methoxyethoxyethoxy)silane, 4-aminobutyltriethoxysilane, acetamidopropyltrimethoxysilane, aminopropylsilanetriol, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, bis(methyldiethoxysilylpropyl)amine, bis(methyldimethoxymethyl)silane silylpropyl) n-methylamine, bis(triethoxysilylpropyl)amine, bis(trimethoxysilylpropyl)urea, bis[(3-trimethoxysilyl)propyl]ethylenediamine, bis[3-(triethoxysilyl)propyl]urea, diethylaminomethyltriethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylsilanetriol, n-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyl Trimethoxysilane, N-(3-aminopropyldimethylsilyl)aza-2,2-dimethyl-2-silacyclopentane, N-(3-triethoxysilylpropyl)4,5-dihydroimidazole, N-(3-trimethoxysilylpropyl)pyrrole, N-(6-aminohexyl)aminomethyltriethoxysilane, N-(6-aminohexyl)aminomethyltrimethoxysilane, N,N,N-trimethyl-3-(trimethoxysilyl)-1-propanaminium, N,N-dioctyl-N'-triethoxysilylpropyl urea, N-[5-(trimethoxysilyl)-2-aza-1-oxopentyl]caprolactam, N-3-[(amino(polypropyleneoxy)]aminopropyltrimethoxysilane, N-butylaminopropyltrimethoxysilane, N-cyclohexylaminopropyltrimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, N-ethylaminoisobutyltrimethoxysilane, N-phenylaminomethyltriethoxysilane, n-trimethoxysilylpropylcarbamoylcaprolactam, ureapropyltriethoxysilane, ureapropyltrimethoxysilane and mixtures thereof, preferably selected from N-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, bis[3-(trimethoxysilyl)propyl]amine,
[0102] The amine-functionalized silane coupling agent and / or the epoxy-functionalized silane coupling agent can be used alone or in combination of two or more in the alkaline pretreatment agent.
[0103] In some embodiments of the present invention, the silane coupling agent, based on the total weight of the solid content, is a silanol group-containing resin having the formula Y-[Si(Y)2-O] n -R means,
[0104] wherein, independently, n is an integer from 1 to 3,
[0105] R is a C1 to C6 alkyl group, preferably a C1 to C3 alkyl group,
[0106] Y is a group selected from the group consisting of an alkyl group having not more than 10 carbon atoms carrying at least one epoxy, amino, hydroxyl, vinyl and / or mercapto group, wherein Y is selected independently of one another.
[0107] In some particularly preferred embodiments, the reagent of the present invention comprises a silane compound selected from vinyltriacetoxysilane, bis-trialkoxysilylpropylamine, aminoethylaminopropyltrialkoxysilane, aminoethylaminopropyltrialkoxysilane, mercaptopropyltrialkoxysilane, bis-trialkoxysilylpropyl-tetrasulfide, 3-glycidoxypropyltrialkoxysilane, wherein the alkoxy group has no more than 3 carbon atoms.
[0108] In some alkaline pretreatment agents of the present invention, the content of the silane coupling agent is 2.0 wt % to 4.5 wt %, or 2.5 wt % to 4.5 wt %, or 2.0 wt % to 4.2 wt %, or 2.5 wt % to 4.0 wt %, or 2.5 wt % to 3.8 wt %, based on the total weight of the solid content of the pretreatment agent.
[0109] In some acidic pretreatment agents of the present invention, the content of the silane coupling agent is 40.0 wt % to 60.0 wt %, or 42.0 wt % to 58.0 wt %, or 45.0 wt % to 55.0 wt %, or 46.0 wt % to 53.0 wt %, based on the total weight of the solid content of the pretreatment agent.
[0110] resin
[0111] The anti-corrosion pretreatment agent further comprises one or more resins selected from the group consisting of a polyurethane resin (A), a polyurethane-acrylic resin (B), and a polyacrylic-epoxy resin (D).
[0112] <Polyurethane Resin (A)>
[0113] The polyurethane resin (A) used in the present invention can be prepared by subjecting an organic compound (polyol) containing two or more hydroxyl groups in its molecule to polyaddition reaction with polyisocyanate, chain extension with diamine or the like, and dispersion in water.
[0114] There is no particular limitation on the polyol as long as it contains two or more hydroxyl groups in its molecule. As the polyol, polycarbonate polyol and polyester polyol are preferred. More specifically, the polyurethane resin (A) is preferably in the form of a polycarbonate-based polyurethane or a polyester-based polyurethane.
[0115] Polycarbonate polyols can be prepared by reacting carbonate compounds with diols. Examples of carbonate compounds include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, diethylene carbonate, etc. Examples of diols include aliphatic diols that can be substituted with lower alcohols; alicyclic diols such as cyclohexanediol, hydrogenated xylene glycol, etc.; and aromatic diols such as xylene glycol, etc. Among these diols, aliphatic diols are preferred, and more preferred are aliphatic diols with a carbon chain length of not less than 4 and not more than 9, such as 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, heptanediol, octanediol, nonanediol, etc.
[0116] Polyester polyols can be prepared by condensing low molecular weight glycols and dicarboxylic acids. Examples of low molecular weight glycols include glycols having not less than 2 and not more than 6 carbon atoms, such as ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,4-butanediol, etc. Among these low molecular weight glycols, preferred are ethylene glycol, propylene glycol, 1,4-butanediol, etc. Examples of dicarboxylic acids include aliphatic dibasic acids, such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, tridecanedioic acid, etc.; and aromatic dibasic acids, such as isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc. Among these dicarboxylic acids, preferred are aliphatic dibasic acids, and more preferred are dibasic acids with a methylene chain length of not less than 4 and not more than 8, such as adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, etc.
[0117] Examples of polyisocyanates include chain aliphatic diisocyanates such as tetramethylene diisocyanate, 1,6-hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate; aliphatic diisocyanates having a cyclic structure such as isophorone diisocyanate, hydrogenated xylene diisocyanate, and dicyclohexylmethane 4,4'-diisocyanate; aliphatic diisocyanates containing aromatic rings such as xylene diisocyanate and tetramethylxylene diisocyanate; aromatic diisocyanates such as toluene diisocyanate and diphenylmethane diisocyanate; and modified products of these diisocyanates (e.g., modified products containing carbodiimide, uretdione, and uretimine). Among these polyisocyanates, preferred are aliphatic diisocyanates and aromatic diisocyanates.
[0118] The polyurethane resin (A) is preferably used in the form of an aqueous dispersion thereof. If necessary, the aqueous dispersion of the polyurethane resin (A) may further contain a dispersant such as a surfactant.
[0119] In some embodiments, the polyurethane resin (A) is an anionic aqueous dispersion. In some embodiments, the polyurethane resin (A) preferably contains an acid group from the perspective of improving its dispersion stability in an aqueous medium and from the perspective of improving the storage stability of the aqueous dispersion and the adhesion and optical density of the aqueous dispersion. As the acid group of the polyurethane resin (A), a carboxyl group is preferred from the perspective of improving the storage stability of the aqueous pigment dispersion and the adhesion and optical density of the aqueous ink.
[0120] The carboxyl group-containing polyurethane resin (A) can be prepared by subjecting a polyol, a polyisocyanate and a dialkol carboxylic acid to a polyaddition reaction. Examples of dialkol carboxylic acids include dimethylol butanoic acid, dimethylol propionic acid and salts of these acids. Examples of reaction solvents for the above-mentioned polyaddition reaction include acetone, methyl ethyl ketone, tetrahydrofuran, dioxane, ethyl acetate, toluene, xylene and the like. In the above-mentioned polyaddition reaction, if necessary, a chain extender or a reaction terminator can also be used in combination with the above-mentioned components. By using a chain extender, the molecular weight of the resulting resin can be increased. As chain extenders, polyols and polyamines can be used. In addition, as reaction terminators, monohydric alcohols and monoamines can be used.
[0121] In some alkaline embodiments, most or even all of the polyurethane resins included in the anti-corrosion pretreatment agent preferably have carboxyl groups. The carboxyl groups are optionally neutralized and reacted, particularly neutralized and reacted with ammonia, amines (particularly alkanolamines) or / and alkali metal compounds to form an aqueous solution with the polyurethane synthetic resin, which can be easily dispersed with water. Before reacting under standard conditions, the carboxyl groups are optionally insoluble in water. The neutralization of the -COOH group is a kind of anionic stabilization reaction. It may also be necessary to additionally add at least one emulsifier or / and at least one protective colloid (as an additive within the scope of the present application) to stabilize the dispersion of the polyurethane synthetic resin and the anti-corrosion pretreatment agent.
[0122] In some acidic embodiments, the polyurethane resin (A) having a cationic group, the polyol, the polyisocyanate, and the polymerization method as monomer components to be formed are not particularly limited. For example, the polyurethane resin (A) can be prepared by selecting corresponding raw materials from the above-mentioned anionic polyurethane resins, polycondensing them in an inert organic solvent (e.g., methyl ethyl ketone), and then reacting the resulting urethane prepolymer with an acid (e.g., formic acid or acetic acid) or a cationizing agent (e.g., dimethyl sulfate) to quaternize some of the tertiary amino groups. Polyols such as polyester polyols, polyether polyols, or polycarbonate polyols; diisocyanates such as aliphatic, alicyclic, or aromatic diisocyanates; and compounds having two or more hydroxyl groups or amino groups and one or more tertiary amine and / or quaternary ammonium groups.
[0123] The amount of cationic groups and the total amine value contribute to the water dispersion stability of the cationic polyurethane resin (A) and its compatibility with other components. In addition, the cationic groups and the total amine value can improve the acid resistance and alkali resistance of the formed pretreatment layer while ensuring storage stability, resulting in excellent corrosion resistance.
[0124] In the preparation process of the present invention, the pH of the aqueous pretreatment agent without the addition of other compounds is preferably greater than 7 to 12, particularly preferably greater than 7 to 11, 7.5 to 10.5, or 8 to 9.5. It should be noted that the polyurethane resin is typically neutralized by the manufacturer, for example, during polymerization. In aqueous formulations without the addition of other compounds, the pH of the aqueous pretreatment agent is preferably between 1 and 12. If the pH of the aqueous composition changes to a value outside the range of greater than 7 to 11 during preparation, it is recommended to restore it to a pH range greater than 7 to 11, or even to a narrower working range within this range, by appropriately adding, but preferably only adding, at least one alkaline substance, as the addition of acids and / or acidic substances may result in undesirable salt formation. If the pH drops due to storage of the synthetic resin and / or mixture, it may be helpful to restore the pH (particularly the pH of the aqueous pretreatment agent before use) to a more alkaline range by adding, for example, aqueous sodium hydroxide.
[0125] In some embodiments of the present invention, the polyurethane resin has a glass transition temperature (Tg) of -100°C to -50°C, or -100°C to -70°C, and an elongation of 300% or more, or 500% or more.
[0126] In some embodiments of the present invention, the weight average molecular weight of the polyurethane resin may be at least 2,000, preferably 5,000-250,000, and particularly preferably 20,000-200,000.
[0127] As used herein, "M w ” refers to weight average molecular weight and is the theoretical value as determined by gel permeation chromatography (GPC) relative to linear polystyrene standards ranging from 1.1 M to 580 Da, which can be performed using a Waters 2695 Separations Module and a Waters 2414 Differential Refractometer (RI detector).
[0128] In some embodiments, the polyurethane resin (A) is an anionic aqueous dispersion, and the polyurethane resin includes polyether-based polyurethane resins and polyester-based polyurethane resins.
[0129] Examples of commercially available polyurethane resins are, for example, Leasys 3900 or Leasys 5531 from Wanhua Chemical, K200 polyurethane resin from Anhui Andahuatai materials.
[0130] The above-mentioned polyurethane resins may be used alone or in any combination.
[0131] In some embodiments, the polyurethane resin (A) is an anionic aqueous dispersion, and the polyurethane resin comprises a polycarbonate-based polyurethane resin.
[0132] Examples of commercially available polycarbonate resins are, for example, Hauthane L-3528 and L-3529 from Hauthaway, Esacote PU A32D and ESACOTE PU 6419 from Lamberti.
[0133] The above-mentioned polycarbonate polyurethane resins may be used alone or in any combination.
[0134] In some embodiments, the polyurethane resin (A) is a cationic aqueous dispersion, and the polyurethane resin includes polyether-based polyurethane resins and polyester-based polyurethane resins.
[0135] Examples of commercially available polyurethane resins are, for example, AH-1730 and AH-1610Y from Anhui Andahuatai materials, PU7305 polyurethane resin from Shanghai Beite New Material Technology, and Wantipro 0380 and Wantipro 0312N from Wanhua Chemical.
[0136] <Polyurethane-acrylic resin (B)>
[0137] In some embodiments, the polyurethane-acrylic resin (B) is an aqueous dispersion of a polyurethane-acrylic resin.
[0138] Polyurethane-acrylic resin can be directly synthesized according to known methods, or can be commercially available.For example, acrylic acid-urethane dispersion can be prepared by polyol, acid, isocyanate and acrylate reaction.Polyol can be one or more selected from the group consisting of the following: polybutylene glycol (PTMG), 1,6-hexanediol, ethylene glycol, propylene glycol, diethylene glycol, butylene glycol (butylene glycol), neopentyl glycol, trimethylolpropane, butylene glycol (butanediol), 1,4-hexanediol and 3-methylpentanediol.The acid can be one or more selected from the group consisting of the following: dimethylolpropionic acid (DMPA), acrylic acid and adipic acid, phthalic acid, isophthalic acid, terephthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, adipic acid, fumaric acid, maleic acid, trimellitic acid, malic acid and aconitic acid. In addition, the isocyanate may be one or more selected from the group consisting of isophorone diisocyanate (IPDI), trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, propylene diisocyanate, ethylene diisocyanate, 2,3-dimethylethylene diisocyanate, 1-methyltrimethylene diisocyanate, 1,3-cyclopentylene diisocyanate, 1,4-cyclopentylene diisocyanate, 1,2-cyclopentylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, oligomeric isocyanates, isophorone diisocyanate, 4,4-diphenylpropane diisocyanate, xylene diisocyanate, and 1,1,6,6-tetramethylhexamethylene diisocyanate. The acrylic acid ester may include a monounsaturated ester of (meth)acrylic acid with an unsubstituted alkyl group, and particularly preferably methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, ethylhexyl (meth)acrylate, 3,3,5-trimethylhexyl (meth)acrylate, stearyl (meth)acrylate, dodecyl (meth)acrylate, and cycloalkyl (meth)acrylate. Suitable monounsaturated esters of (meth)acrylic acid with a substituted alkyl group may preferably be substituted with one or more hydroxyl groups, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, as well as 2-hydroxyethyl (meth)acrylate. The total mass of the (meth)acrylate preferably has a content of 5.0 to 70.0 wt %, more preferably 30.0 to 50.0 wt %, based on the total weight of the polyurethane-acrylic resin (B).Furthermore, the (meth)acrylate should be selected so that the glass transition temperature Tg of the resulting polyurethane-acrylic resin (B) is 5°C to 45°C, preferably 10°C to 40°C.
[0139] In some embodiments, the polyurethane-acrylic resin (B) preferably includes a mixed or cross-linked (meth)acrylic resin and a polyurethane resin.
[0140] More preferably, the acid groups contained in the (meth)acrylic resin and the urethane resin are partially cross-linked with the cross-linking agent.
[0141] In some embodiments of the present invention, the aqueous dispersion of polyurethane-acrylic resin comprises polyester-polyurethane-poly(meth)acrylate, polyester-polycarbonate-polyurethane-polyacrylate, and corresponding derivatives.
[0142] Examples of commercially available polyurethane-acrylic resins are, for example, BS PUAW Tt-10 and SGR-0215W from Shanghai Xinyang Chemical, or SGR-3002W from Changle Chemical, or Neopac E-123 and Neopac E-129 from DSM.
[0143] The above-mentioned polyurethane-acrylic resins may be used alone or in any combination.
[0144] In some embodiments of the present invention, the above-mentioned polyurethane-acrylic resin (B) and polyurethane resin (A) may be used alone or in any combination.
[0145] In some embodiments, the polyurethane-acrylic resin (B) is a cationic aqueous dispersion of a polyurethane-acrylic resin. This cationic acrylic polyurethane dispersion can be prepared by reacting a polyol, a cationizing agent (hydrophilic chain extender), an isocyanate, and an acrylate. The choice of hydrophilic chain extender depends on the pH of the anti-corrosion pretreatment agent. In some acidic embodiments, a cationizing agent is preferred to form a cationic aqueous dispersion; in some alkaline embodiments, an anionizing agent is preferred to form an anionic aqueous dispersion.
[0146] <Polyacrylic acid-epoxy resin (D)
[0147] The anti-corrosion pretreatment agent of the present invention further comprises a polyacrylic-epoxy resin (D).
[0148] In some embodiments of the present invention, the polyacrylic-epoxy resin (D) is an aqueous dispersion.
[0149] In some embodiments of the present invention, the polyacrylic-epoxy resin (D) of the present invention comprises a carboxyl-containing polymer comprising repeating units derived from a carboxyl-containing vinyl monomer. In other words, the polyacrylic-epoxy resin (D) comprises a carboxyl-containing polymer chain as part of its structure.
[0150] The glass transition temperature (Tg) of the waterborne polyacrylic-epoxy resin (D) is not particularly limited, but is preferably 50° C. to 100° C. The method for preparing the waterborne polyacrylic-epoxy resin (D) is not particularly limited, and any known method is applicable.
[0151] For example, epoxy resin is reacted with at least a vinyl monomer containing a glycidyl group, a vinyl monomer containing an amide group or a vinyl monomer containing an amino group and a glycidyl ether of a polyalkylene glycol, and an amine is added as a catalyst to obtain a vinyl monomer containing a carboxyl group. The monomer and the vinyl monomer containing a carboxyl group are then polymerized. For vinyl monomers containing glycidyl groups, it is possible to use without restriction as long as glycidyl groups and polymerizable vinyl groups are contained in its molecule, including glycidyl (meth) acrylate, 3-methyl glycidyl (meth) acrylate and (meth) allyl glycidyl ether. For vinyl monomers containing amide groups, it is possible to use without restriction as long as amide groups and polymerizable vinyl groups are contained in its molecule, including acrylamide, N-butoxymethyl (meth) acrylamide, N-methyl (meth) acrylamide, N,N-dimethyl (meth) acrylamide, N-isopropyl (meth) acrylamide, diacetone (meth) acrylamide and N-vinyl formamide. The amino group-containing vinyl monomers contain an amino group and a polymerizable vinyl group in their molecules, including N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate.
[0152] The above-mentioned polyacrylic-epoxy resins may be used alone or in any combination.
[0153] Examples of commercially available polyurethane-acrylic resins are, for example, waterborne polyurethane-epoxy resin MR1487W from KDD functional materials, GS-5000B, GS-500D from Guangxiu Chemical, and ACUST 3958 from Wuxi Honghui New Materials Technology.
[0154] In some embodiments of the present invention, the above-mentioned polyacrylic-epoxy resin (D), polyurethane-acrylic resin (B), and polyurethane resin (A) may be used alone or in any combination.
[0155] In some acidic aqueous anti-corrosion pretreatment agents of the present invention, the content ratio of the resin is 0% to 48% by weight, or 0% to 45% by weight, or 0% to 42% by weight, or 20% to 42% by weight, based on the total weight of the resin and the bifunctional epoxy resin precursor (C) in the anti-corrosion pretreatment agent. The lower limit of the resin concentration, based on the total weight of the resin and the bifunctional epoxy resin precursor (C) in the anti-corrosion pretreatment agent, is 0% by weight, or 15% by weight, or 20% by weight, or 25% by weight. The upper limit of the resin concentration, based on the total weight of the resin and the bifunctional epoxy resin precursor (C) in the anti-corrosion pretreatment agent, is 48% by weight, or 45% by weight, or 42% by weight, or 40% by weight, or 38% by weight.
[0156] In some alkaline aqueous anti-corrosion pretreatment agents, the content ratio of the resin is 25 wt% to 55 wt%, or 28 wt% to 53 wt%, based on the total weight of the resin and the bifunctional epoxy resin precursor (C) in the anti-corrosion pretreatment agent. The lower limit of the concentration of the resin, based on the total weight of the resin and the bifunctional epoxy resin precursor (C) in the anti-corrosion pretreatment agent, is 25 wt%, or 27 wt%, or 28 wt%, or 30 wt%, or 33 wt%. The upper limit of the concentration of the resin, based on the total weight of the resin and the bifunctional epoxy resin precursor (C) in the anti-corrosion pretreatment agent, is 55 wt%, or 54 wt%, or 53 wt%, or 50 wt%.
[0157] Optional additives
[0158] The anti-corrosion pretreatment agent of the present invention may further contain optional additives.
[0159] The anti-corrosion pretreatment agent / solution may optionally contain conventional additives known to those skilled in the art of adhesives. Conventional additives compatible with the disclosed surface treatment composition / solution can be determined simply by combining potential additives with the composition and determining whether they remain uniform. Non-limiting examples of suitable additives include, but are not limited to, solvents, corrosion inhibitors, defoamers, surfactants, UV stabilizers, extenders, and plasticizers known in the art.
[0160] The total content of the additives will vary depending on the amount of each specific additive required to provide a light metal anti-corrosion pretreatment agent / solution having the desired properties. The additive content can be from 0 to about 10 weight percent, preferably from about 0.1 to about 5 weight percent, based on the total weight of the anti-corrosion pretreatment agent.
[0161] Preparation method of bifunctional epoxy resin precursor
[0162] The bifunctional epoxy resin precursor can be prepared by repeating the addition reaction and condensation reaction of a bifunctional epoxy. The epoxy of the present invention is not particularly limited in type as long as it contains two epoxy groups in its molecule, including bisphenol A, bisphenol F and epichlorohydrin (epichlorohydrin) (e.g., epihalohydrin) and epoxy compounds with two or more glycidyl groups.
[0163] In some embodiments of the present invention, the difunctional epoxy resin precursor is preferably prepared by the following steps:
[0164] The difunctional epoxy is reacted with a nucleophilic or electrophilic compound having an active hydrogen atom; and a pH adjuster and water are added to the solution to obtain a neutralized difunctional epoxy resin precursor having a solid content of 5 to 32 weight percent.
[0165] In some embodiments of the present invention, the difunctional epoxy resin precursor is represented by the formula:
[0166] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2
[0167] Among them, independently,
[0168] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms;
[0169] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms (preferably 1 to 10 carbon atoms) or H;
[0170] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms;
[0171] X = -COO-, a sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-, preferably -COO-, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- comprises an aliphatic chain having 1 to 5 carbon atoms;
[0172] Y = -COO-, a sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-, preferably -COO-, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; the R group in -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O- comprises an aliphatic chain having 1 to 5 carbon atoms;
[0173] R3 is any type of chain as long as it connects two hydroxyl α-carbon atoms; preferably, R3 is selected from the group consisting of: aromatic or aliphatic groups having 1 to 20 carbon atoms, polyurethane groups, aliphatic or aromatic alkanes having 2 to 20 carbon atoms, and acrylate-containing polymer groups.
[0174] n is an integer of 1 to 10, preferably an integer of 2 to 8.
[0175] Preparation method of anti-corrosion pretreatment agent
[0176] The anti-corrosion pretreatment agent can be prepared by dispersing all resin materials, metal compounds, silane coupling agents and other raw materials (if necessary) in water or a water-soluble solvent. Solid content is adjusted by removing solvent and volatile components. Solvent is typically water, and some small amounts of water-based solvents (such as alcohols, ketones and water-soluble organic solvents based on cellosolves) can be used in combination to reduce film forming time. The solid content concentration of the aqueous anti-corrosion pretreatment agent is not particularly limited, but is preferably in the range of 15 weight % to 50 weight %, or 15 weight % to 40 weight %, or 25 weight % to 35 weight %.
[0177] The method for forming the intermediate layer is not particularly limited. Examples include roll coating, dipping, and spraying, followed by drying with a hot air furnace, induction heating furnace, and infrared heater. The peak temperature of the steel plate is 40-150°C, but preferably within the range of 50-80°C.
[0178] In some embodiments of the present invention, the anti-corrosion pretreatment agent is preferably prepared by the following steps:
[0179] a) dissolving the resin compound and other compounds in water under stirring to obtain a solution;
[0180] b) adjusting the solution obtained in step a) by using an ammonia solution to achieve an appropriate pH value, wherein the pH value of the solution is preferably from 8 to 12, preferably greater than 9 to 12, or more preferably from 9 to 10;
[0181] c) Adding a silane coupling agent under stirring to achieve a balance between hydrolysis and condensation.
[0182] d) Add other additives if necessary and stir to obtain a homogeneous solution without stratification.
[0183] Metal surface coating and curing methods
[0184] The method according to the invention is particularly suitable for coating metal sheets selected from zinc or zinc alloy sheets, aluminum or aluminum alloy sheets, and steel strip coated with zinc or zinc alloys or coated with aluminum or aluminum alloys. In this context, "zinc alloy" or "aluminum alloy" is understood to mean an alloy consisting of more than 50 atomic % zinc or aluminum.
[0185] For the test panels, the following materials (i) to (v) were used.
[0186] i. Cold rolled steel plate (SPCC): plate thickness 0.8mm;
[0187] ii. Electro-galvanized steel sheet (EG): thickness 0.8mm;
[0188] iii. Galvanized steel sheet (HDG): thickness 0.6mm;
[0189] iv. Galvanized steel sheet (GL): thickness 0.6mm;
[0190] v. Zinc-magnesium-aluminum alloy (ZAM): plate thickness 0.5mm.
[0191] The test plate was processed according to the following steps (1) to (5).
[0192] 1) Degrease the metal surface of the test plate;
[0193] 2) Rinse with tap water;
[0194] 3) Dry the metal surface with compressed air;
[0195] 4) Roll-coating the pretreatment agent on the surface of the test plate;
[0196] 5) drying the pretreatment agent by passing it through hot air or in an oven,
[0197] Therein, during step (5), the temperature is preferably at least 75°C, but not more than 240°C, preferably not more than 150°C.
[0198] In some embodiments of the present invention, a pretreatment agent for treating a metal plate is applied to a new surface of the metal plate using a bar coater, and the test plate is dried in a hot air dryer so that the peak metal temperature (PMT) of the test plate is 95°C.
[0199] Coating thickness measurement
[0200] To measure coating thickness, we first prepared a cross-section sample using an X-ray spectrometer (ZSX Primus III+; Rigaku Corporation, Japan). Three points on the panel were selected to measure the coating thickness. The minimum value was the lower limit, and the maximum value was the upper limit.
[0201] The dry film thickness is 0.05-1.0 μm. The preferred film thickness is 0.1-0.4 μm.
[0202] Formation of topcoat layer
[0203] After forming the pretreatment coating (cured anti-corrosion pretreatment agent), the topcoat material and primer were applied to a dry thickness of 15 μm using a bar coater, and then the sample was heated and dried in a hot air drying oven to a peak plate temperature of 230°C. The topcoat was a polyurethane coating for home appliances from Nippon.
[0204] Implementation Plan List
[0205] 1. An anti-corrosion pretreatment agent comprising:
[0206] a) solvent;
[0207] b) at least one inorganic inhibitor;
[0208] c) at least one silane compound;
[0209] d) a bifunctional epoxy resin precursor (C), wherein the bifunctional epoxy resin precursor (C) is represented by the following formula:
[0210] R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2
[0211] Among them, independently,
[0212] X=-COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-;
[0213] Y=-COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-;
[0214] R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H;
[0215] R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms;
[0216] R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4;
[0217] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;
[0218] n is an integer of 1 to 10.
[0219] 2. The anti-corrosion pretreatment agent according to embodiment 1, wherein independently, R2 is an aromatic chain or an aliphatic chain having 1 to 10 carbon atoms or H, R4 is an aromatic chain or an aliphatic chain having 1 to 10 carbon atoms, R1 is an aromatic chain or an aliphatic chain having 1 to 10 carbon atoms, -XH or -X-R4.
[0220] 3. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, wherein R3 is selected from the group consisting of an aromatic or aliphatic group having 1 to 20 carbon atoms, a polyurethane group, an aliphatic or aromatic alkane having 2 to 20 carbon atoms, and an acrylate-containing polymer group.
[0221] 4. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, wherein X is selected from -COO-, -P(OR)(OH)-O-; and n is an integer from 2 to 8.
[0222] 5. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, wherein the bifunctional epoxy resin precursor (C) is represented by the following formula:
[0223] (H)X-R4-X-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -H
[0224] Among them, independently,
[0225] X=-COO-, -P(OR)(OH)-O-;
[0226] R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms;
[0227] R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms;
[0228] n is an integer from 2 to 8.
[0229] 6. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, further comprising at least one resin selected from the group consisting of polyurethane resin (A), polyurethane-acrylic resin (B), and polyacrylic-epoxy resin (D).
[0230] 7. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, wherein the pH value of the anti-corrosion pretreatment agent is greater than 7 to 12.
[0231] 8. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, wherein the pH value of the anti-corrosion pretreatment agent is 3 to less than 7.
[0232] 9. The anti-corrosion pretreatment agent according to embodiment 7, wherein the content of the bifunctional epoxy resin precursor (C) is 45 wt% to 75 wt% based on the total weight of the bifunctional epoxy resin precursor (C) and the resin.
[0233] 10. The anti-corrosion pretreatment agent according to embodiment 8, wherein the content of the bifunctional epoxy resin precursor (C) is 52 wt% to 100 wt% based on the total weight of the bifunctional epoxy resin precursor (C) and the resin.
[0234] 11. The anti-corrosion pretreatment agent according to embodiment 7 or 9, wherein the anti-corrosion pretreatment agent comprises 2.0 wt% to 4.5 wt% of a silane coupling agent based on the total weight of the solid content, and the silanol group-containing resin is represented by the following formula XY(Z): n Si(OH) 3-n express,
[0235] wherein independently, X is a glycidoxy group or a functional group derived from a glycidoxy group, Y is a C1 to C10 alkylene group, Z is a methoxy group, an ethoxy group or a methyl group, and n is an integer from 0 to 2.
[0236] 12. The anti-corrosion pretreatment agent according to embodiment 8 or 10, wherein the anti-corrosion pretreatment agent comprises 40.0 wt% to 60.0 wt% of a silane coupling agent based on the total weight of the solid content, and the silanol group-containing resin is represented by the following formula: Y-[Si(Y)2-O] n -R means,
[0237] wherein, independently, n is an integer from 1 to 3,
[0238] R is a C1 to C6 alkyl group, preferably a C1 to C3 alkyl group,
[0239] Y is a group selected from the group consisting of an alkyl group having not more than 10 carbon atoms and carrying at least one epoxy, amino, hydroxyl, vinyl and / or mercapto group,
[0240] Among them, Y is selected independently of each other.
[0241] 13. The anti-corrosion pretreatment agent according to embodiment 7, 9 or 11, wherein the anti-corrosion pretreatment agent comprises 0.3 to 7 wt% of an inorganic inhibitor comprising a zirconium compound and / or a vanadium compound, based on the total weight of the solid content in the composition.
[0242] 14. The anti-corrosion pretreatment agent according to embodiment 13, wherein the zirconium compound is selected from the group consisting of ammonium zirconium carbonate, potassium zirconium carbonate, basic zirconium carbonate, zirconium acetate, and combinations thereof.
[0243] 15. The anti-corrosion pretreatment agent according to embodiment 8, 10 or 12, wherein the anti-corrosion pretreatment agent comprises 0.1 to 1.0 mol / L weight % of an inorganic inhibitor, wherein the inorganic inhibitor comprises at least one water-soluble or water-dispersible fluorinated acid or a salt thereof, wherein the fluorinated acid is defined by the following general empirical formula: m T q F p O n , wherein: q and p each represent an integer from 1 to 10; m and n each represent an integer from 0 to 10; and T is an element selected from Ti, Zr, Hf, Si, Sn, Al, Ge and B.
[0244] 16. The anti-corrosion pretreatment agent according to any one of the preceding embodiments, wherein the solid content of the anti-corrosion pretreatment agent is 15 wt% to 50 wt%, based on the total weight of the anti-corrosion pretreatment agent.
[0245] 17. A method for providing corrosion protection and enhancing coating adhesion on a metal surface, the method comprising the steps of:
[0246] a) contacting the anti-corrosion pretreatment agent according to any one of the preceding embodiments with a metal surface at a process temperature of at least 40° C. but not higher than 200° C., thereby forming a film on the metal surface;
[0247] b) optionally removing excess anti-corrosion pretreatment agent from the surface; and
[0248] c) curing the coating on the surface by thermal means or high energy irradiation at a process temperature of 50-90° C. for at least 10 −5 seconds to form a cured coating.
[0249] 18. The method according to embodiment 17, wherein the layer thickness of the cured coating is at least 0.1 μm but not more than 0.5 μm.
[0250] 19. An article comprising at least a portion thereof comprising the treated metal surface of embodiment 17.
[0251] 20. The article according to embodiment 19, wherein the protective coating has a layer thickness of at least 0.1 μm but not more than 0.5 μm.
[0252] 21. The article according to any one of embodiments 19 to 20, wherein the article is used in household appliance applications, and the treated metal surface has a T-bend value (new) equal to or less than 1T when tested according to GB / T13448-2006 standard, and a T-bend value (aged, after aging for 24 hours at 50±2°C and 95% humidity) equal to or less than 2T when tested according to GB / T13448-2006 standard.
[0253] 22. The article according to any one of embodiments 19 to 20, wherein the article is for construction applications, and the treated metal surface has a T-bend value (new) equal to or less than 3T when tested according to GB / T 13448-2006, and a T-bend value (aged, after aging for 24 hours at 50±2°C and 95% humidity) equal to or less than 4T when tested according to GB / T 13448-2006.
[0254] 23. An article, at least a portion of which comprises a pretreatment coating, wherein the protective coating is a cured product of the anti-corrosion pretreatment agent according to any one of embodiments 1 to 16.
[0255] Example:
[0256] The present invention will be described in further detail and explained with reference to the following examples. These examples are intended to help those skilled in the art better understand and practice the present invention, but are not intended to limit the scope of the invention. Unless otherwise stated, all numerals in the examples are by weight.
[0257] raw materials
[0258]
[0259]
[0260] *All raw materials are used directly without any special treatment.
[0261] Example 1
[0262] <Preparation of bifunctional epoxy resin precursor>
[0263] The bifunctional epoxy resin precursor C1 (C1) was synthesized by the following steps:
[0264] Adipic acid and 40g of propylene glycol monomethyl ether were placed in a 100ml round-bottom four-necked flask and heated at 90°C. 260g of YD-128A, a type A epoxy liquid resin (from Guodu) with an epoxy equivalent weight of 190, was then slowly added, and the temperature was maintained at 95°C for 2 hours. After the reaction, 180g of a 28wt% aqueous ammonia solution was slowly added at 40°C, followed by water, to produce an ammonia-neutralized bifunctional epoxy resin precursor C1 with a solids content of 5%-32%. The weight-average molecular weight of bifunctional epoxy resin precursor C1 was 13,000.
[0265] The bifunctional epoxy resin precursor C2 (C2) was synthesized by the following steps:
[0266] Orthophosphoric acid and 100g of propylene glycol monomethyl ether were slowly added to 1250g of type A epoxy resin with an epoxy equivalent weight of 500 and maintained at 95°C for 2 hours. After the reaction, 40g of a 28% aqueous ammonia solution was slowly added at 140°C, followed by water, to obtain an ammonia-neutralized, phosphoric acid-modified bifunctional epoxy resin precursor C2 with a solids content of 5%-32%. The weight-average molecular weight of the bifunctional epoxy resin precursor (C2) was 20,000.
[0267] <Preparation of Anticorrosion Pretreatment Agent>
[0268] The preparation steps of the anti-corrosion pretreatment agent are as follows:
[0269] a) 6.7 g of AH-730 (liquid, from Anhui Andahuatai New Materials), 11.7 g of difunctional epoxy resin precursor C1 (prepared as described above), 2 g of Dynasylan GLYEO (liquid, from Evonik), 2 g of Dynasylan A (liquid, from Evonik), and 2 g of JH A 111 (liquid, from Hubei Jianghan New Material) were charged and mixed for 6 hours to form an aqueous dispersion;
[0270] b) 1.6 g of hexafluorotitanic acid solution, 60 wt.% in H2O (liquid, from Shanghai Aladdin Bio-Chem Technology Co., LTD) was added to the aqueous dispersion prepared in step a).
[0271] <Coating and curing of metal surfaces>
[0272] Test materials
[0273] Galvanized steel sheet (GA): sheet thickness 0.8mm; coating weight 90 / 45g / m 2 ;
[0274] Galvalume steel sheet (GL): thickness 0.6mm;
[0275] Zinc-magnesium-aluminum alloy (ZAM): plate thickness 0.5mm.
[0276] The metal surface treatment process preferably includes the following subsequent steps (1)-(5):
[0277] 1) Degrease the metal surface with RIDOLINE 1559 degreaser from Henkel;
[0278] 2) Rinse with tap water;
[0279] 3) Dry the metal surface with compressed air;
[0280] 4) Roller-coat the primer / pretreatment agent onto the substrate;
[0281] 5) Curing by hot air / oven,
[0282] Wherein, during step (5), the temperature is about 85°C.
[0283] The anti-corrosion pretreatment agent was applied to a new substrate using a bar coater and dried in a hot air dryer to achieve a peak metal temperature (PMT) of 95°C for the test panel.
[0284] To measure coating thickness, first create a cross-section sample using an X-ray spectrometer (ZSX Primus III+; Rigaku Corporation, Japan). Three points on the panel are selected to measure the coating thickness. The minimum value is the lower limit, and the maximum value is the upper limit.
[0285] The dry film thickness ranges from 0.1μm to 0.4μm.
[0286] The primer layer was applied to a dry thickness of 5 μm using a bar coater, and the sample was heat-dried in a hot air drying oven to a peak plate temperature of 230° C. The primer was a chrome-free polyester-based primer from Nippon for home appliance applications, and the primer was NPEP 750 from Nippon for architectural applications.
[0287] The topcoat material was applied to a dry thickness of 15 μm using a bar coater, and the sample was heat-dried in a hot air drying oven to a peak plate temperature of 230° C. The topcoat was a polyester paint for home appliance applications from Nippon, and the topcoat was PCM500 for architectural applications from Nippon.
[0288] Examples 2-23 and CE1-CE26
[0289] The pretreatment agents for E2 to E23 and CE1 to CE26 were prepared according to Example 1. The metal surfaces of E2 to E23 and CE1 to CE26 were treated according to Example 1. More details are listed in the results section below.
[0290] Various tests were carried out on the prepared samples.
[0291] Test Method
[0292] Adhesion
[0293] <T-bend value (new)> and <T-bend value (aged)>
[0294] According to the requirements of the bending test method in GB / T 13448-2006 "Test Methods for Color Coated Steel Sheets and Strips", a 180-degree bending test was carried out using a T-type bending testing machine. At the same time, the samples were placed in a test chamber, the temperature was set at 50±2°C, and the humidity was 95%, and an accelerated aging test was carried out for 24 hours. After taking out the samples, a T-type bending test (aged T-bend value) was carried out. The T-type bending test equipment was the WZJ-II T-type bending machine from Shanghai Xiandai Environment Engineering Technique Co., Ltd.
[0295] The results records and rankings of the T-bend value (new) for household appliance applications are as follows:
[0296] - Unqualified: greater than 1T.
[0297] - Qualified: less than or equal to 1T.
[0298] - Good: equal to 0T.
[0299] The results records and rankings of the T-bend value (new) for building applications are as follows:
[0300] - Unqualified: greater than 3T.
[0301] - Qualified: less than or equal to 3T.
[0302] - Good: equal to 1T.
[0303] - Excellent: equal to 0T.
[0304] The results records and rankings of the T-bend value (aged) for household appliance applications are as follows:
[0305] - Unqualified: greater than 2T.
[0306] - Qualified: less than or equal to 2T.
[0307] - Good: less than or equal to 1T.
[0308] -Excellent: equal to 0T.
[0309] The T-bend value (aging) results for architectural applications are recorded and ranked as follows:
[0310] - Unqualified: greater than 4T.
[0311] -Qualified: less than or equal to 4T.
[0312] -Good: equal to 2T.
[0313] -Excellent: equal to 1T.
[0314] <Cross-cupping test>
[0315] According to the bending test requirements of GB / T 13448-2006, "Test Methods for Color-Coated Steel Sheets and Strips," a cross-hatch cupping test was conducted using a BYK-Gardner GmbH electro-hydraulic cupping tester, Cat. No. 5400. The cross-hatch cupping test method and ranking criteria are the same for both appliance and construction applications.
[0316] The results of the cross-hatch-cupping test were recorded and ranked as follows:
[0317] Failure (F): The peeling area is greater than 5%.
[0318] Pass (P): The peeling area is less than or equal to 5%.
[0319] Good (G): The peeling area is less than or equal to 2%.
[0320] Very good (VG): The peeled area is equal to 0%.
[0321] <Reverse impact test>
[0322] The reverse impact test involves dropping a weight onto the strip from a height three times the thickness of the metal. The coating on the deformed surface is inspected for cracks or breaks. Adhesive tape is then applied to the deformed area and removed. If any coating is removed from the strip surface, the sample fails the test. The energy impact tester is an Elcometer 1615. The weight is 1 kg, the height is 90 cm, and the impact energy is 9 J. The reverse impact test method and ranking criteria are the same for appliance and construction applications.
[0323] Evaluation criteria:
[0324] Good (G): The paint layer is not peeling and there are no cracks.
[0325] Unqualified (F): There are cracks or paint peeling.
[0326] Corrosion resistance
[0327] <Cross neutral salt spray test 240 hours and 1000 hours>
[0328] Each test panel (150 mm x 70 mm) with a cross-shaped "X" cut was subjected to a neutral salt spray test (GBT 10125-1997) for 240 hours for appliance applications and 1000 hours for architectural applications. The cut line length exceeded 50 mm. The maximum expansion width of the cross-line was measured and evaluated according to the following standards. The corrosion test equipment was a Q-fog SSP salt spray test chamber from Q-Lab. Trimming guard: According to the requirements of GB / T 6461, level 10. The evaluation criteria were the same for both appliance and architectural applications.
[0329] Very good (VG): less than or equal to 1mm.
[0330] Good (G): less than or equal to 2 mm.
[0331] Pass (P): less than or equal to 3mm.
[0332] Unqualified (F): greater than 3mm.
[0333] <500 hours and 1000 hours neutral salt spray test on board>
[0334] Each test panel (150mm x 70mm) was subjected to a neutral salt spray test (GBT10125-1997) for 500 hours (for appliance applications) or 1000 hours, and visually inspected and evaluated as follows. The evaluation criteria were the same for appliance applications and architectural applications.
[0335] Evaluation criteria:
[0336] Very Good (VG): No foaming.
[0337] Good (G): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is less than 5.
[0338] Pass (P): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is equal to or greater than 5 and less than 10.
[0339] Unqualified (F): The size of a single bubble is equal to or greater than 1.0 mm, and the number of bubbles generated is equal to or greater than 10 and less than 20.
[0340] <Scrap edge neutral salt spray test 240 hours (home appliance application)>
[0341] Each test panel (150 mm x 70 mm) with a cut edge was subjected to a neutral salt spray test (GBT 10125-1997) for 240 hours (appliance to household appliances) and visually inspected and evaluated as follows.
[0342] Evaluation criteria:
[0343] Very good (VG): less than or equal to 3mm.
[0344] Good (G): less than or equal to 6 mm.
[0345] Pass (P): greater than 6mm and less than 10mm.
[0346] Unqualified (F): equal to or greater than 10mm.
[0347] <1000 hours of cut edge neutral salt spray test (for architectural applications)>
[0348] Each test panel (150 mm x 70 mm) with a cut edge was subjected to a neutral salt spray test (GBT 10125-1997) for 1000 hours (building application) and visually inspected and evaluated as follows.
[0349] Evaluation criteria:
[0350] Very good (VG): less than or equal to 5mm.
[0351] Good (G): less than or equal to 8 mm.
[0352] Pass (P): greater than 8mm and less than 12mm.
[0353] Unqualified (F): equal to or greater than 12mm.
[0354] Solvent resistance
[0355] <Surface resistance to solvent wiping (MEK)>:
[0356] The equipment used was a DJH MEK friction tester from DJH Designs Inc., with a set speed of one stroke per second, a pressure of 0.1 ± 0.02 MPa, and a test length of at least 150 mm. For color-coated panels used in architectural applications, 100 strokes were performed, while for color-coated panels used in appliance applications, 50 strokes were performed.
[0357] Evaluation criteria:
[0358] Good (G): No marks, or traces of wiping without paint peeling.
[0359] Unqualified (P): The topcoat is peeling off.
[0360] Chemical resistance
[0361] <Alkali resistance>
[0362] Each test plate was immersed in a 5 wt% NaOH aqueous solution at room temperature for 24 hours. The size and density of the generated bubbles were then visually inspected, and the alkali resistance was evaluated in the following manner.
[0363] Evaluation criteria:
[0364] Very Good (VG): No foaming.
[0365] Good (G): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is less than 5.
[0366] Pass (P): The size of a single bubble is 1.0 mm, and the number of bubbles generated is equal to or greater than 5 and less than 10.
[0367] Failure (F): The size of a single bubble is 1.0 mm or larger, or the number of bubbles generated is greater than 10.
[0368] <Sulfuric acid resistance test> and <Hydrochloric acid resistance test>
[0369] Each test plate was immersed in a 5 wt % aqueous sulfuric acid solution at room temperature for 24 hours, and then the size and density of generated bubbles were visually inspected and evaluated based on criteria similar to those for alkali resistance.
[0370] Each test plate was immersed in a 5% by mass hydrochloric acid aqueous solution at room temperature for 24 hours, and then the size and density of generated bubbles were visually inspected and evaluated based on criteria similar to those for alkali resistance.
[0371] Very Good (VG): No foaming.
[0372] Good (G): The size of a single bubble is less than 1.0 mm, and the number of bubbles generated is less than 5.
[0373] Pass (P): The size of a single bubble is 1.0 mm, and the number of bubbles generated is equal to or greater than 5 and less than 10.
[0374] Failure (F): The size of a single bubble is 1.0 mm or larger, or the number of bubbles generated is greater than 10.
[0375] result
[0376] Table 1.
[0377]
[0378] Table 1 shows the compositions of the anti-corrosion pretreatment agents E1-E11.
[0379] Table 2.
[0380]
[0381]
[0382] Table 2 shows the test results of the anti-corrosion pretreatment agents E1-E11.
[0383] In Examples 1 to 11, the anti-corrosion pretreatment agents were prepared according to the formulations provided herein and exhibited excellent adhesion properties. Even after aging, the adhesion properties on various substrates still met the requirements for construction and appliance applications. Furthermore, Examples E1-E11 exhibited excellent corrosion resistance.
[0384] Table 3.
[0385]
[0386]
[0387] Table 3 shows the compositions of the anti-corrosion pretreatment agents CE1-CE13.
[0388] Table 4.
[0389]
[0390]
[0391] Table 4 shows the test results of the anti-corrosion pretreatment agents CE1-CE13.
[0392] Table 5.
[0393] E12 E13 E14 E15 E16 E17 E18 E19 E20 E21 E22 E23 Hauthane L-3528 4 Hauthane L-3529 3 4 Esacote PU A32D 4 4 3 4 4 3 BS PUAW TT-10 4 4 C1 8 8 8 8 5.5 8 8 8 8 8 C2 8 8 MR1487W 4 4 JH-O1871 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Dynasylan GLYEO 0.5 0.5 0.5 0.5 0.5 Zircosol AC 20 0.6 0.6 0.6 0.6 0.6 0.6 Zirconium(IV) acetate 0.6 0.6 0.6 0.6 0.6 Vanadium (V) oxide 0.2 0.2 0.2 0.2 0.2 0.2 Vanadium acetylacetonate (3) 0.2 0.2 0.2 0.2 0.2 0.2 Total solid content 13.3 13.3 13.3 13.3 13.3 12.8 13.3 13.3 13.3 13.3 13.3 11.7 Total reagents 86.7 86.7 86.7 86.7 86.7 87.2 86.7 86.7 86.7 86.7 86.7 88.3 C: total resin + C 66% 66% 66% 66% 66% 47% 66% 66% 66% 66% 66% 72% pH 8.0 7.5 8.0 7.5 8.0 7.5 7.5 8.0 7.5 8.0 8.0 8.0 Film thickness (μm) 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4 0.1-0.4
[0394] Table 5 shows the compositions of the anti-corrosion pretreatment agents E12-E23.
[0395] Table 6.
[0396]
[0397]
[0398]
[0399] Table 6 shows the test results of the anti-corrosion pretreatment agents E12-E23.
[0400] Table 7.
[0401]
[0402] Table 7 shows the compositions of the CE14-CE26 anti-corrosion pretreatment agents.
[0403] Table 8.
[0404]
[0405]
[0406] Table 8 shows the test results of the CE14-CE26 anti-corrosion pretreatment agents.
Claims
1. An anti-corrosion pretreatment agent, comprising: e) solvent; f) at least one inorganic inhibitor; g) at least one silane compound; h) a bifunctional epoxy resin precursor (C), wherein the bifunctional epoxy resin precursor (C) is represented by the following formula: R1-Y-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -R2 in, Independently, X = -COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; Y=-COO-, sulfur group, -NR(H)-, -P(OR)2-O-, -P(OR)(OH)-O-, -PO-O-; R2 is an aromatic or aliphatic chain having 1 to 20 carbon atoms or H; R4 is an aromatic or aliphatic chain having 1 to 20 carbon atoms; R1 is an aromatic or aliphatic chain having 1 to 20 carbon atoms, -XH or -X-R4; R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms; n is an integer of 1 to 10.
2. The anti-corrosion pretreatment agent according to claim 1, wherein Independently, R2 is an aromatic or aliphatic chain having 1 to 10 carbon atoms or H, R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms, R1 is an aromatic or aliphatic chain having 1 to 10 carbon atoms, -XH or -X-R4.
3. The anti-corrosion pretreatment agent according to claim 1, wherein R3 is selected from the group consisting of an aromatic or aliphatic group having 1 to 20 carbon atoms, a polyurethane group, an aliphatic or aromatic alkane having 2 to 20 carbon atoms, and an acrylate-containing polymer group.
4. The anti-corrosion pretreatment agent according to claim 1, wherein X is selected from -COO-, -P(OR)(OH)-O-; and n is an integer from 2 to 8.
5. The anti-corrosion pretreatment agent according to claim 1, wherein The bifunctional epoxy resin precursor (C) is represented by the following formula: (H)X-R4-X-[CH2-CH(OH)-R3-CH(OH)-CH2-X-R4-X] n -H Among them, independently, X=-COO-, -P(OR)(OH)-O-; R4 is an aromatic or aliphatic chain having 1 to 10 carbon atoms; R3 is any type of chain as long as it connects the two hydroxyl α-carbon atoms; n is an integer of 2-8.
6. The anti-corrosion pretreatment agent according to claim 1, wherein The anti-corrosion pretreatment agent further comprises at least one resin selected from the group consisting of polyurethane resin (A), polyurethane-acrylic resin (B), and polyacrylic-epoxy resin (D).
7. The anti-corrosion pretreatment agent according to any one of claims 1 to 6, wherein The pH value of the anti-corrosion pretreatment agent is greater than 7 to 12.
8. The anti-corrosion pretreatment agent according to any one of claims 1 to 6, wherein The pH value of the anti-corrosion pretreatment agent is 3 to less than 7.
9. The anti-corrosion pretreatment agent according to claim 7, wherein: The content of the bifunctional epoxy resin precursor (C) is 45 to 75 wt % based on the total weight of the bifunctional epoxy resin precursor (C) and the resin.
10. The anti-corrosion pretreatment agent according to claim 8, wherein: The content of the bifunctional epoxy resin precursor (C) is 52 wt % to 100 wt % based on the total weight of the bifunctional epoxy resin precursor (C) and the resin.
11. The anti-corrosion pretreatment agent according to claim 7, wherein: Based on the total weight of the solid content, the anti-corrosion pretreatment agent contains 2.0 wt % to 4.5 wt % of a silane coupling agent, and the silanol group-containing resin is represented by the following formula XY(Z): n Si(OH) 3-n express, Wherein, independently, X is a glycidoxy group or a functional group derived from a glycidoxy group, Y is a C1 to C10 alkylene group, Z is a methoxy group, an ethoxy group or a methyl group, and n is an integer from 0 to 2.
12. The anti-corrosion pretreatment agent according to claim 8, wherein: Based on the total weight of the solid content, the anti-corrosion pretreatment agent contains 40.0 wt % to 60.0 wt % of a silane coupling agent, and the silanol group-containing resin is represented by the following formula: Y-[Si(Y)2-O] n -R means, wherein, independently, n is an integer from 1 to 3, R is a C1 to C6 alkyl group, preferably a C1 to C3 alkyl group, Y is a group selected from the group consisting of an alkyl group having not more than 10 carbon atoms and carrying at least one epoxy, amino, hydroxyl, vinyl and / or mercapto group, wherein the Y's are selected independently of each other.
13. The anti-corrosion pretreatment agent according to claim 7, wherein: The anti-corrosion pretreatment agent comprises 0.3 to 7 wt % of an inorganic inhibitor based on the total weight of the solid content in the composition, and the inorganic inhibitor comprises a zirconium compound and / or a vanadium compound.
14. The anti-corrosion pretreatment agent according to claim 13, wherein: The zirconium compound is selected from the group consisting of ammonium zirconium carbonate, potassium zirconium carbonate, basic zirconium carbonate, zirconium acetate and combinations thereof.
15. The anti-corrosion pretreatment agent according to claim 8, wherein: The anti-corrosion pretreatment agent comprises 0.1 to 1.0 mol / L weight % of an inorganic inhibitor, wherein the inorganic inhibitor comprises at least one water-soluble or water-dispersible fluorinated acid or a salt thereof, wherein the fluorinated acid is defined by the following general empirical formula: m T q F p O n , wherein: q and p each represent an integer from 1 to 10; m and n each represent an integer from 0 to 10; and T is an element selected from Ti, Zr, Hf, Si, Sn, Al, Ge and B.
16. The anti-corrosion pretreatment agent according to claim 1, wherein: The solid content of the anti-corrosion pretreatment agent is 15 wt % to 50 wt % based on the total weight of the anti-corrosion pretreatment agent.
17. A method for providing corrosion protection and enhancing coating adhesion on a metal surface, the method comprising the steps of: a) contacting the anti-corrosion pretreatment agent according to any one of claims 1 to 16 with a metal surface at a process temperature of at least 40° C. but not higher than 200° C., thereby forming a film on the metal surface; b) optionally removing excess of the anti-corrosion pretreatment agent from the surface; as well as c) curing the coating on the surface by a thermal method or high energy irradiation at a process temperature of 50-90° C. for at least 10-5 seconds to form a cured coating.
18. The method according to claim 17, wherein: The layer thickness of the cured coating is at least 0.1 μm but not more than 0.5 μm.
19. An article comprising at least a portion thereof comprising the treated metal surface of claim 17.
20. The article of claim 19, wherein: The layer thickness of the protective coating is at least 0.1 μm but not more than 0.5 μm.
21. The article of claim 20, wherein: The product is used for household appliance applications, and the T-bend value (new) of the treated metal surface when tested according to GB / T13448-2006 standard is equal to or less than 1T, and the T-bend value (aged, after aging for 24 hours at 50±2°C and 95% humidity) when tested according to GB / T13448-2006 standard is equal to or less than 2T.
22. The article of claim 20, wherein: The product is used for construction applications, and the T-bend value (new) of the treated metal surface when tested according to GB / T13448-2006 standard is equal to or less than 3T, and the T-bend value (aged, after aging for 24 hours at 50±2°C and 95% humidity) when tested according to GB / T13448-2006 standard is equal to or less than 4T.
23. An article, at least a portion of which comprises a pretreatment coating, wherein: The protective coating is a cured product of the anti-corrosion pretreatment agent according to any one of claims 1 to 16.
Citation Information
Patent Citations
Chromium-free coil coating composition
DE19751153A1
chrome-free anti-corrosion agent and anti-corrosion process
DE19754108A1
Polymerizable composition for the anticorrosion coating of metallic substrates contains an organic titanium, silicon or zirconium compound
DE19923118A1